POPULATION STATUS OF COLLARED Pecari tajacu AND WHITE-LIPPED PECCARIES Tayassu pecari IN THE PERUVIAN AMAZON - PEREZ-PEÑA, Pedro (2017)
The collared peccary (Pecari tajacu) and white-lipped peccary (Tayassu pecari) are very important species as a source of protein and economic income for rural household, and are culturally important in Amazonian Communities. Despite their importance, and due to the scarcity of information on their populations in a large part of the Peruvian Amazon, it is difficult to evaluate the sustainable use as bushmeat and for the export of skins. In this way, this study aims to evaluate populations of P. tajacu and T. pecariin the regions of Loreto and Ucayali by using fixed-width line transects in 33 localities and through interviews to determine the 'cultural consensus' for the abundance of the species in 11 localities. Of a total of 14,220.5 km of 2 linear transects traveled in the study sites, showed that the population density of P. tajacu was 1.24 ind/km 2 being registered in 32 (96.9%) localities, while T. pecarishowed a population density of 1.59 ind/km and was registered in 16 (48.5%) localities. Only the density of P. tajacu was related to the group size. The 162 interviews conducted in 11 communities showed that the population density of P. tajacu was abundant, while the perception of abundance of T. pecari was from frequent to abundant. The population densities of the two species of peccaries were greater in the non-flooded forests than in the flooded forest, and both species showed a positive correlation. According to the study methods used, there were no differences in the population size reported for the two species of peccaries, both inside and outside the natural protected areas. This indicates that areas outside the natural protected areas that contain high population densities are of a great importance for the conservation of peccaries, and contribute to ensuring food security for rural and indigenous communities.